If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 3x + 8 Reorder the terms: -3 + 2x = 3x + 8 Reorder the terms: -3 + 2x = 8 + 3x Solving -3 + 2x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + 2x + -3x = 8 + 3x + -3x Combine like terms: 2x + -3x = -1x -3 + -1x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -1x = 8 + 0 -3 + -1x = 8 Add '3' to each side of the equation. -3 + 3 + -1x = 8 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 8 + 3 -1x = 8 + 3 Combine like terms: 8 + 3 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| x(x-9)(x+1)=0 | | 7Y+17=2Y-18 | | 18-6n=12n-18 | | 9b+40=136 | | (4w-5)+(9w+2)=0 | | 1.8*2.4= | | 8x-(3x+4)=11 | | X^2+13=0 | | 27x-29x=10-12 | | -4x-6+x=-4x+x-10 | | -3x-9+x=-4x+x-10 | | 4y+28+12z= | | 9x^4+3x^3-30x^2+6x+12=0 | | 7c-7=17-c | | 2x^3+x^2+12x+6=0 | | 15m-20m=51 | | 8a-3a+9a=0 | | 2x^4-5x^3-17x^2+41x-21=0 | | 2y(3y+1)=9y+3 | | x+x+2x=4x | | x^3-5x^3-17x^2+41x-21=0 | | 24w+24z= | | t+4t=8 | | x^3-5x^2+7x-35=0 | | 3t+12t+t+4t=8 | | 3(2x-7)=2x+43 | | (4x-6)(9x+1)=0 | | -7x-7=-84 | | 600=115x-22915 | | 2x^4-50=0 | | 41X+23=9X+407 | | 12x^2-15x+3.125=0 |